Pengaruh Kompetensi, Independensi, dan Moral Reasoning Auditor Terhadap Kualitas Audit : Studi pada Kantor Inspektorat Provinsi Sulawesi Selatan - Muh Alif Saputra; Basmar, Nur Azizah (Insan Cita Bongaya Research Journal, 2024)
This study aims to test whether Competence, Independence, and Moral reasoning of auditors affect the quality of audits at the South Sulawesi Provincial Inspectorate Office. Data collection uses primary data in the form of questionnaires. The population used in this study is auditors who work at the Regional Inspectorate office of South Sulawesi Province which totals 35 auditors. The sampling technique uses saturated samples. So the number of samples used in this study is 35 auditors. Data analysis in this study uses descriptive statistics, validity and reliability tests and classical assumption tests. The data analysis method in hypothesis testing uses multiple linear regression analysis. The results of the study showed that competence had a significant positive effect on audit quality, independence had a significant positive effect on audit quality and auditor moral reasoning had a significant positive effect on audit quality